The diagnosis of autism spectrum disorders - Volkmar, Fred (Henry Stewart Talks, 2021)
Diagnosing autism, The history of autism, Hans Asperger, Leo Kanner, DSM-5, ICD-10, Categorical approach to autism, Dimensional approach to autism, PDD-NOS, Autism spectrum disorder, Asperger’s disorder, Dimensional assessment instruments